2017
DOI: 10.1021/acs.jchemed.6b00566
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Chemistry Skills Gap: The Duality between Expected and Desired Skills

Abstract: Results from an employer survey that examines the skills gap that exists for students majoring in chemistry are presented. Employers expect candidates with technical abilities but desire those who possess strong interprofessional skills. Although employers do not expect students to have had explicit teaching and application of interprofessional skills, employers wish that chemistry programs incorporated them. The results show which particular skills, specific to chemists and in relation to other fields, make u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 9 publications
2
61
0
4
Order By: Relevance
“…It has been reported that employers tend to be satisfied with the technical knowledge and skills of graduates while being dissatisfied with the level of so-called such as the ability to work with others, that they bring with them to the workplace (Archer and Davison, 2008), including employers of chemistry graduates (see Overton and McGarvey (2017) and references therein). A recent survey revealed that employers of chemists reported interpersonal skills, teamwork, and a strong work ethic as the three most desirable attributes of new hires, with 76% of respondents reporting that teamwork and interpersonal skills are more important than grade point average (Kondo and Fair, 2017). In the same survey, 95% of respondents reported that they expected or desired that explicit training and feedback on teamwork skills be part of chemistry programmes, and the data indicated that team experiences relating to chemistry topics were valued more highly than those obtained in relation to other areas of study or through military or sporting activities.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that employers tend to be satisfied with the technical knowledge and skills of graduates while being dissatisfied with the level of so-called such as the ability to work with others, that they bring with them to the workplace (Archer and Davison, 2008), including employers of chemistry graduates (see Overton and McGarvey (2017) and references therein). A recent survey revealed that employers of chemists reported interpersonal skills, teamwork, and a strong work ethic as the three most desirable attributes of new hires, with 76% of respondents reporting that teamwork and interpersonal skills are more important than grade point average (Kondo and Fair, 2017). In the same survey, 95% of respondents reported that they expected or desired that explicit training and feedback on teamwork skills be part of chemistry programmes, and the data indicated that team experiences relating to chemistry topics were valued more highly than those obtained in relation to other areas of study or through military or sporting activities.…”
Section: Introductionmentioning
confidence: 99%
“…These attributes have been observed to be important for industry and for graduate success 1 . However, recent research has highlighted the difficulty in incorporating assessment of the development of these skills as they "require feedback and personal reflection that are often difficult to incorporate given the technically dense material of the field" 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Having students working in the social environment of the laboratory can encourage them to develop good communication goals that aligns with what faculty and future employers have identified as desirable skills for students. [7][8][9]200 Findings suggest that the experimental context produced different patterns of interaction between the TAs and the students. Even though students participated in some surface level interpretation of the data during the laboratory period, as evidenced from the laboratory observations and MLLI results, there was very little evidence from the observations and Actions coding scheme of the students actually connecting underlying concepts to the data they were collecting while they were in the laboratory.…”
Section: Discussionmentioning
confidence: 94%
“…Upper-level courses offer a chance for students to hone process skills, such as information processing, problem solving, and critical thinking, that will assist them both in and out of the classroom and that are not limited to a particular course or discipline. These skills are desired by both faculty [8][9][39][40] and future employers 7 . Faculty who were involved in both the ANA-POGIL and ELIPSS projects wanted a way to improve students' process skills by providing them with feedback.…”
Section: Purpose Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation